1995
DOI: 10.1111/j.1524-4725.1995.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Freehand Technique to Harvest Partial-Thickness Skin to Repair Superficial Facial Defects

Abstract: In selected sites and patients, the freehand graft is a rapid and convenient method of harvesting skin. When harvested from the preauricular cheek and subauricular neck, the graft is a good match to cover sun-exposed defects of the nose and ear. The major advantages of the freehand technique are that: 1) it expands the number of potential donor sites from which to select the most compatible skin to cover facial defects; 2) it allows the surgeon to efficiently configure the graft to the desired shape and depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In most cases, the preauricular or postauricular skin is favored because they generally provide a satisfactory match for facial skin, especially of the nose and ear. 1,4 The donor areas are delineated using a marking pen and anesthetized using tumescent infiltration of 1% lidocaine with epinephrine (1:200,000 dilution). Betadyne or hebiclens is used as a topical antiseptic.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, the preauricular or postauricular skin is favored because they generally provide a satisfactory match for facial skin, especially of the nose and ear. 1,4 The donor areas are delineated using a marking pen and anesthetized using tumescent infiltration of 1% lidocaine with epinephrine (1:200,000 dilution). Betadyne or hebiclens is used as a topical antiseptic.…”
Section: Methodsmentioning
confidence: 99%
“…15 scalpel blade in a bevelled or vertical incision to enter the dermis and then slicing the upper dermis at a blunter vertical angle when at the desired level of the dermis to harvest the graft. They suggested that the angle allows for stabilization of the dermis as the graft is harvested, but decreases the velocity at which the graft is harvested . Our technique differs from theirs in that we use an initial vertical score to outline the size and shape of the STSG required, and use a dressing without bolster on the graft site.…”
mentioning
confidence: 99%
“…2a-c) and the feet. 4 For auricular reconstruction, the sites used for harvesting score and shave STSGs included the postauricular neck and postauricular scalp areas. The donor site for the digits and feet were from the lateral thigh.…”
mentioning
confidence: 99%
See 2 more Smart Citations